Interpolations between Jordanian Twists Induced by Coboundary Twists - Borowiec, A.; Meljanac, D.; Meljanac, S.; Pachoł, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We propose a new generalisation of the Jordanian twist (building on the previous idea from [Meljanac S., Meljanac D., Pachoł A., Pikutić D., J. Phys. A: Math. Theor. 50 (2017), 265201, 11 pages]). Obtained this way, the family of Jordanian twists allows for interpolation between two simple Jordanian twists. This new version of the twist provides an example of a new type of star product and the realization of noncommutative coordinates. Real forms of new Jordanian deformations are also discussed. Exponential formulae, used to obtain coproducts and star products, are presented with details.